Hubungan Antara Resiliensi Dengan Minat Berwirausaha Pada Mahasiswa - Taufiq, Imam; , Dr. Wiwien Dinar Pratisti, M.Si, Psi (2017)
Students armed with knowledge and science that owned at least a student into an embryo to be born into a true entrepreneur and not fully dependent with getting jobs from other people. The purpose of this research was to determine: 1) relationship between the resilience with an interest in entrepreneurship students. 2) student interest in entrepreneurship. 3) level of resilience possessed by students. 4) effective contribution of the resilience of the interest in entrepreneurship students. The hypothesis is a positive relationship between resilience with an interest in entrepreneurship students. Subjects in this research were 60 students. The population in this study is the final year students of the Faculty of Psychology University of Muhammadiyah Surakarta. The measuring instruments used in this research are: a)Scale resilience and b)Scale Interests entrepreneurship. Data analysis techniques used in this research is the product moment correlation. The results of analysis in accordance with the proposed hypothesis, namely, there is a very significant positive relationship between resiliensi with interest in entrepreneurship students. The higher the resiliensi then the higher interest in entrepreneurship for students, instead the lower resiliensi the low interest in entrepreneurship. Based on the research results and conclusions to be drawn that the pembahsan; 1) there is a very significant positive relationship between resiliensi with interest in entrepreneurship in students. The higher the resiliensi then the higher interest in entrepreneurship in students and instead the lower resiliensi the low interest in entrepreneurship in students. 2) entrepreneurship Interest on a student belongs. 3) Resiliensi on a student belongs. 4) Role or contribution of effective resiliensi against the interest in entrepreneurship at the student level end of 34.4%, while the rest of 65.6% are affected by other variables.